(3GdaQL HYO GdTOIs - (3GdeMSf Hf Ydj Hf eMeO Hf CHj Gdage OGhO GdJfhNj GdHUQj, CHh Ydj,J (B384 (3g` s ((3eMeO Hf HQcGJ GdLQjQj s)
(3ChdgG (B:s
(3CeG HYO, aEfj deG QCjJ CHfGA GdOfjG eJbdHjf ajgG Hjf NjQ hTQ, hfaY hVQ s
(3BNQgG (B:s
(3EPG JVGjb GeQD aGfJXQ aQLG aCVjb GdCeQ COfGg Edi GdaQL s
(3JJab aj ChdgG hJNJda aj BNQgG eY GdfSNI GdChdis
(3fSNI KGfjI HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B288 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B185s
Keywords: (3GdCOHs